Reply to the comment on 'Two-state vector formalism and quantum interference'. (12th January 2018) - Hashmi, F A; Li, Fu; Zhu, Shi-Yao; Suhail Zubairy, M
Abstract: In the preceding comment it is claimed that we are mistaken in the analysis of the theory of the 'past of a quantum particle' proposed by the author of the comment. We show that the claim is unfounded. Moreover we show that the arguments presented in the comment are not consistent with the already proposed theory.